HIV pre-exposure prophylaxis: assessment of acceptability among members of HIV serodiscordant/serostatus unknown couples. (June 2022) - Bracho-Sanchez, Edith; Stonbraker, Samantha; Halpern, Mina; Wood, Sarah; Lowenthal, Elizabeth
Background: Pre-exposure prophylaxis (PrEP) is effective in preventing HIV infection but is not yet widely available in resource-limited settings such as the Dominican Republic. We aimed to ascertain PrEP acceptability among people living with HIV in the Dominican Republic who are part of HIV serodiscordant partnerships and understand relationships between PrEP acceptability, HIV stigma, and intimate partner violence.Methods: A cross-sectional survey of people in care for HIV infection included acceptability-related questions and assessments of HIV stigma and intimate partner violence. We also explored the expected impact of PrEP on HIV disclosure rates and fertility intentions.Results: Of the 100 participants, 74% had been in their current partnership for >1 year; 38% had not disclosed to their partner; 29% reported condomless sex, and 23% reported sex with multiple partners. PrEP was highly acceptable with 84% of participants saying they were "very likely" to offer PrEP to their partner if available and 21% stating it would allow them to have more children. Of those who had not disclosed to their partner, 71% stated PrEP would help them do so. No relationship was found between PrEP acceptability, HIV stigma, and intimate partner violence. However, higher than expected rates of PrEP acceptability limited the power of these analyses.Conclusion: Pre-exposure prophylaxis was considered to be highly acceptable among people living with HIV in the Dominican Republic who are part of serodiscordant partnerships.